Structural and Biochemical Characterization of a Cyanobacterial PP2C Phosphatase Reveals Insights into Catalytic Mechanism and Substrate Recognition - Yunlong Si (Catalysts, 2016)
PP2C-type phosphatases play roles in signal transduction pathways related to abiotic stress. The cyanobacterial PP2C-type phosphatase tPphA specifically dephosphorylates the PII protein, which is a key regulator in cyanobacteria adapting to nitrogen-deficient environments. Previous studies have shown that residue His39 of tPphA is critical for the enzyme’s recognition of the PII protein; however, the manner in which this residue determines tPphA substrate specificity is unknown. Here, we solved the crystal structure of H39A, a tPphA variant. The structure revealed that the mutation of residue His39 to alanine changes the conformation and the flexibility of the loop in which residue His39 is located, and these changes affect the substrate specificity of tPphA. Moreover, previous studies have assumed that the FLAP subdomain and the third metal (M3) of tPphA could mutually influence each other to regulate PP2C catalytic activity and substrate specificity. However, despite the variable conformations adopted by the FLAP subdomain, the position of M3 was consistent in the tPphA structure. These results indicate that the FLAP subdomain does not influence M3 and vice versa. In addition, a small screen of tPphA inhibitors was performed. Sanguinarine and Ni2+ were found to be the most effective inhibitors among the assayed chemicals. Finally, the dimeric form of tPphA was stabilized by cross-linkers and still exhibited catalytic activity towards p-nitrophenyl phosphate.